Frequency of Exposure Influences Accentedness and Comprehensibility in Learners' Pronunciation of Second Language Words. Issue 1 (30th August 2022) - Uchihara, Takumi; Webb, Stuart; Saito, Kazuya; Trofimovich, Pavel
Abstract: The current study investigated the effects of repetition on the learning of second language (L2) spoken word forms. Japanese university students learning L2 English were randomly assigned to one of three treatment conditions (one, three, and six exposures) and learned 40 words while hearing them and viewing their corresponding pictures. A picture‐naming test was administered before, immediately after, and approximately one week after the treatment. The elicited speech samples were evaluated for two aspects of spoken vocabulary knowledge: pronunciation (accentedness and comprehensibility) and form–meaning connection (spoken form recall). Results showed that (a) the number of exposures positively affected measures of form–meaning connection and pronunciation immediately after the treatment, and (b) cognateness moderated how strongly repetition impacted the pronunciation of L2 words. Moderate learning gains occurred for comprehensibility after six exposures to new words. However, with six exposures, only small effects of repetition were observed for accentedness. Abstract :